(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2018)
Research background. The causes of fibromyalgia (FM) are unclear and diagnosing FM is complicated, which limits treatment options, and no treatment to date has proven fully effective in alleviating its symptoms. In current studies, where art therapy has been applied in the case of FM, art therapy has been part of a multidisciplinary intervention. The authors were unable to find any published data on the effects of art therapy on FM. The aim of the research was to determine the effect of group art therapy on pain, emotional state, and feeling of health and comfort of FM patients. Research methods. Intervention included ten structured art therapy sessions. The participants were 20 women between the ages of 39–64 years. In order to assess the results of therapy, a self-rate questionnaire was used. Therapy session changes were registered using pain and fatigue NRS and semantic differential scales of feeling of health and comfort. The outcome of group art therapy was assessed with a pain and fatigue NRS, and an Emotional State Questionnaire (EST-Q2). An open question was used to study the expectations of participants at the beginning of therapy and the main result of the therapy upon its conclusion. Research results. During the group art therapy session, pain and fatigue decreased and the feeling of health and comfort improved. This was confirmed by the content analysis of open questions. Following therapy, a significant decrease had taken place in the subscales of the Emotional State Questionnaire in depression, anxiety, and agoraphobia-panic; a substantial decrease in pain and fatigue took place in patients with heightened baseline measures. Conclusion. The changes following the therapy session confirm the results of earlier studies on the positive effects of psychotherapy and art therapy sessions on pain. The pilot study provided promising results for the application of structured short-term group art therapy with FM patients. Keywords: group art therapy, fibromyalgia, pain, fatigue, emotional state. Keywords: group art therapy, fbromyalgia, pain, fatigue, emotional state.